ChemInform Abstract: Challenges in the Search for Magnetic Coupling in 3d/4f Materials: Syntheses, Structures, and Magnetic Properties of the Lanthanide Copper Heterobimetallic Compounds, RE2Cu(TeO3)2(SO4)2. Issue 22 (3rd June 2014) - Lin, Jian; Chai, Ping; Diefenbach, Kariem; Shatruk, Michael; Albrecht‐Schmitt, Thomas E.
Abstract Ln2Cu(TeO3)2(SO4)2 (Ln: Y, Nd, Sm—Lu) with two different structural topologies are prepared by hydrothermal treatment of Ln2O3, CuO, and TeO2 in aqueous H2SO4 (autoclave, 230 °C, 3 d, cooling rate of 5 °C/h).